A new subspecies of the reticulatus group, genus Atractus, from Southeastern South America (Serpentes, Colubridae) - Álvarez, Blanca Beatriz (1992)
A new subspecies of the genus Atractus reticulatus group from Corrientes (Argentina) and Rio Grande do Sul (Brasil), identified and described. Its relationships with the Southeastern Brasilian nominate form and other poorly known regional forms of the genus are analysed and discussed.